Skill-based employment taxonomy in the global IT industry 5.0 - Valverde-Rebaza, Jorge; Rodrigues de Góes, Fabiana; Noguez, Julieta; Da Silva, Nathalia C. (Frontiers in Education, 2025)
IntroductionThe Information Technology (IT) sector, a key driver of Industry 4.0 and the transition toward Industry 5.0, continues to demonstrate resilience in the face of prevalent global challenges, including the ongoing COVID-19 pandemic and persistent talent shortages. The prominence of IT roles in the global job market highlights the need for a unified framework that efficiently identifies and categorizes IT jobs. While the International Labour Organization (ILO) has introduced the International Standard Classification of Occupations (ISCO) for job classification on a global scale, it lacks the necessary granularity for the rapidly evolving IT landscape.MethodsEfforts to bridge the previous granularity issue often fall short due to country-specific labor market peculiarities. To address this gap, this work introduces a novel hierarchical taxonomy for classifying IT jobs within the broader framework of ISCO-08. Following meticulous data labeling and clustering, the development of the Bee-inspired Employment and Expertise Taxonomy (BEET) was a collaborative effort between the HR team, data scientists, analysts, and the authors of this article. A lot of public job postings were gathered that encompass a diverse range of vacancies within the IT sector, spanning from October 2023 to February 2025. Using insights from the clustering results, the team worked to identify distinct patterns and commonalities across IT job roles. Our taxonomy consists of five major groups, further divided into 15 sub-major groups and 35-unit groups. The proposed taxonomy has the potential to not only categorize diverse IT roles with precision but also forecast workforce demands effectively.ResultsKey insights suggest that this hierarchical approach could significantly aid in workforce demand forecasting and provide valuable guidance to educators in shaping programs that prepare professionals for the challenges of Industry 5.0. Furthermore, by aligning educational efforts with the evolving needs of the global IT market, our proposal offers a robust framework for both analysts and educators, providing strategic insights essential for future workforce development in the rapidly advancing.DiscussionThe development of the BEET taxonomy marks a significant advancement as a framework for IT job classification, offering a comprehensive and adaptable tool aligned with the evolving demands of the technology sector in the era of Industry 5.0. By leveraging the BEET framework, we can gain deeper insights into the dynamics of the IT labor market, enabling more targeted and impactful research. However, some limitations should be noted, as the dataset used to develop BEET consists exclusively of English-language job postings from various countries, which may introduce linguistic and regional biases. Additionally, certain niche or emerging roles that are less frequently advertised online may be underrepresented in the taxonomy.